반 영역 체적조절호형 방사선치료의 선량학적 효과 분석 - 장현수 (The Graduate School, Ajou University, 2020)
Background: Although there are some controversies regarding whole pelvic radiation therapy (WPRT) due to its gastrointestinal toxicities, it is combined with other systemic treatment to find an effective strategy for patients with gynecological, rectal, and prostate cancer. To effectively spare organ at risk (OAR), doses using multileaf collimator’s optimal segments and volumetric modulated arc therapy (VMAT) using a half-beam technique (HF) were implemented for WPRT. Methods and Materials: Dosimetric benefits of HF-VMAT were presented with dose conformity and dose volume parameters in terms of modulation complex score, as compared to VMAT optimized using a fully opened field (FF). The size of the FF was decided to entirely include a planning target volume plus a 3-mm margin in all beam’s eye view at arc angles. Half of the FF from the isocenter was opened for dose optimization in HF-VMAT. Consequent normal tissue complication probabilities (NTCPs) by reduction of the irradiated volumes and delivered doses for OAR were evaluated Results: Compared to FF-VMAT, HF-VMAT showed superior conformal dose distribution where the 75% isodose line compactly surrounded the separated regional lymph nodes. Dose conformity was comparable between HF-VMAT and FF-VMAT, however, HF-VMAT used 60%-70% less intensity modulation than that used by FF-VMAT. The small intestine and colon showed noticeable reduction in the irradiated volumes of up to 35% and 15%, respectively, at an intermediate dose of 20-45 Gy. The small intestine showed statistically significant dose sparing at the volumes that received a dose every 5 Gy from 15 to 45 Gy. Such a dose reduction for the small intestine and colon in HF-VMAT presented significant NTCP reduction than that in FF-VMAT. Conclusions: VMAT dose optimization using the HF technique more optimal composition of multileaf collimator segments to deliver conformal doses without excessive intensity modulation. It achieved distinguishable dose sparing for gastrointestinal OAR in WPRT without sacrificing the target dose conformity. HF-VMAT can be useful in reducing OAR toxicities associated with WPRT.
학위논문(박사)--아주대학교 일반대학원 :의학과,2020. 2